2018
DOI: 10.1093/gerona/gly171
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association Between Nut Consumption and Physical Function in Older Men and Women

Abstract: Nut consumption was associated with half the risk of impaired agility and mobility in men and with lower risk of overall physical function impairment in women. The suggested protective effect of nut consumption on physical functioning merits further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…This section will review observational studies that examined the association between nut consumption, either alone ( Section 3.1.1 ) or as part of a dietary pattern ( Section 3.1.2 ), and sarcopenia and related factors in older adults. A total of seven observational studies have been identified ( Table 2 ) [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. To the best of our knowledge, no intervention studies have been specifically designed to determine the effect of nut consumption on sarcopenia.…”
Section: Nut Consumption and Sarcopenia And Related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This section will review observational studies that examined the association between nut consumption, either alone ( Section 3.1.1 ) or as part of a dietary pattern ( Section 3.1.2 ), and sarcopenia and related factors in older adults. A total of seven observational studies have been identified ( Table 2 ) [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. To the best of our knowledge, no intervention studies have been specifically designed to determine the effect of nut consumption on sarcopenia.…”
Section: Nut Consumption and Sarcopenia And Related Factorsmentioning
confidence: 99%
“…Seven observational studies have been identified in the nuts and sarcopenia area ( Table 2 ) [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. One prospective study examined the association between nut consumption and physical function [ 60 ], three observational studies (one prospective study and two cross-sectional studies) reported nuts as a food group [ 62 , 63 , 65 ], and another three studies (one prospective study and two cross-sectional studies) examined the adherence to diet quality indices in which nuts was a key component [ 61 , 64 , 66 ]. Two studies were conducted in Spain, and one each in the United States, China, Korea, Denmark, and Iran ( Table 2 ).…”
Section: Nut Consumption and Sarcopenia And Related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in traditional bioactive herbal compounds with less detrimental effects on human body than their synthetic counterparts is growing. Many clinical trials and cohort studies showed that consumption of foods (vegetables, fruits, nuts) rich in biologically active molecules with demonstrated antioxidant capacity, through different mechanisms of actions, has the potential to protect against cardiometabolic diseases, neurodegenerative disorders, cancer, or age-related sarcopenia and frailty [1,2,3,4,5]. Increased intake of antioxidants from tree nuts and peanuts influences risk factors associated with aging and can extend health span and lifespan [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the potential limitations, diet was self-reported, so certain misclassification and social desirability bias may have occurred. It should be noted, however, that the information from this validated diet history has been used previously to assess the impact of dietary variables on frailty and functional status in older adults (5,15,(54)(55)(56)(57) . Also, results were similar when using the cumulative consumption of legumes in 2010 and 2013 as the independent variable.…”
Section: Discussionmentioning
confidence: 99%